Recycling of Waste Streams of the Biotechnological Poly(hydroxyalkanoate) Production by Haloferax mediterranei on Whey. (3rd March 2015) - Koller, Martin
Abstract : For manufacturing "bioplastics" such as poly(hydroxyalkanoates) (PHA), the combination of utilization of inexpensive carbon sources with the application of robust microbial production strains is considered a decisive step to make this process more cost-efficient and sustainable. PHA production based on surplus whey from dairy industry was accomplished by the extremely halophile archaeon Haloferax mediterranei . After fermentative production of PHA-rich biomass and the subsequent cell harvest and downstream processing for PHA recovery, environmentally hazardous, highly saline residues, namely spent fermentation broth and cell debris, remain as residues. These waste streams were used for recycling experiments to assess their recyclability in subsequent production processes. It was demonstrated that spent fermentation broth can be used to replace a considerable part of fresh saline fermentation medium in subsequent production processes. In addition, 29% of the expensive yeast extract, needed as nitrogen and phosphate source for efficient cultivation of the microorganism, can be replaced by cell debris from prior cultivations. The presented study provides strategies to combine the reduction of costs for biomediated PHA production with minimizing ecological risks by recycling precarious waste streams. Overall, the presented work shall contribute to the quick economic success of these promising biomaterials.